Advancing research and clinical care in the management of neuropathic pain after spinal cord injury: Key findings from a Canadian summit. Issue 1 (1st January 2017) - Loh, Eldon; Guy, Stacey D.; Craven, B. Cathy; Guilcher, Sara; Hayes, Keith C.; Jeji, Tara; Joshi, Phalgun; Kras-Dupuis, Anna; Laramée, Marie-Thérèse; Lee, Joseph; Mehta, Swati; Noonan, Vanessa K.; et al.
ABSTRACT: Background : Optimal management of neuropathic pain (NP) is essential to enhancing health-related quality of life for individuals living with spinal cord injury (SCI). A key strategic priority for the Ontario Neurotrauma Foundation (ONF) and Rick Hansen Institute (RHI) is optimizing NP management after SCI. Aims : A National Canadian Summit, sponsored by ONF and RHI, was held to develop a strategic plan to improve NP management after SCI. Methods : In a one-day meeting held in Toronto, Ontario, a multidisciplinary panel of 18 Canadian stakeholders utilized a consensus workshop methodology to (1) describe the current state of the field, (2) create a long-term vision, and (3) identify steps for moving into action. Results : A review of the current state of the field identified strengths including rigourously developed evidence syntheses and practice landscape documentation. Identified gaps included limited evidence on NP hindering recommendation development in evidence syntheses, absence of a national strategy, care silos with limited cross-continuum connections, limited consumer involvement, and limited practice standard implementation. The panel identified key themes for a long-term vision to improve the management of SCI NP in Canada, including establishing an integrated collaborative network; standardized care and outcome evaluation; education; advocacy; and directing resources to innovative solutions. The panel identified the next step as prioritization of areas that will have the greatest impact in a 5-year time frame. Conclusion : A strategic plan outlining a long-term vision to improve management of NP after SCI in Canada was developed and will inform future activities of the sponsors.